Parahydrogen-induced polarization study of imine hydrogenations mediated by a metal-free catalyst. Issue 36 (8th September 2022) - Zakharov, Danila O.; Chernichenko, Konstantin; Sorochkina, Kristina; Repo, Timo; Zhivonitko, Vladimir V.
Abstract : Imine hydrogenations with parahydrogen mediated by a metal-free ansa -aminoborane catalyst (QCAT) lead to nuclear spin hyperpolarization of amine products and catalytic intermediates. These observations provide mechanistic insights into the reaction. Abstract : Parahydrogen-induced polarization is a nuclear spin hyperpolarization technique that can provide strongly enhanced NMR signals for catalytic hydrogenation reaction products and intermediates. Among other matters, this can be employed to study the mechanisms of the corresponding chemical transformations. Commonly, noble metal complexes are used for reactions with parahydrogen. Herein, we present a PHIP study of metal-free imine hydrogenations catalyzed by the ansa -aminoborane catalyst QCAT. We discuss the reaction mechanism by showing the pairwise nature of the initial hydrogen activation step that leads to the formation of the negative net nuclear spin polarization of N–H hydrogen in the QCAT-H2 intermediate, enabling the further transfer of parahydrogen-originating protons to the imine substrate with the accumulation of hyperpolarized amine products. Parahydrogen-induced polarization also demonstrates the reversibility of the catalytic cycle.